Novel AAV capsids for intravitreal gene therapy of photoreceptor disorders. Issue 4 (22nd February 2021) - Pavlou, Marina; Schön, Christian; Occelli, Laurence M; Rossi, Axel; Meumann, Nadja; Boyd, Ryan F; Bartoe, Joshua T; Siedlecki, Jakob; Gerhardt, Maximilian J; Babutzka, Sabrina; Bogedein, Jacqueline; Wagner, Johanna E; et al.
Abstract: Gene therapy using recombinant adeno‐associated virus (rAAV) vectors to treat blinding retinal dystrophies has become clinical reality. Therapeutically impactful targeting of photoreceptors still relies on subretinal vector delivery, which detaches the retina and harbours substantial risks of collateral damage, often without achieving widespread photoreceptor transduction. Herein, we report the development of novel engineered rAAV vectors that enable efficient targeting of photoreceptors via less invasive intravitreal administration. A unique in vivo selection procedure was performed, where an AAV2‐based peptide‐display library was intravenously administered in mice, followed by isolation of vector DNA from target cells after only 24 h. This stringent selection yielded novel vectors, termed AAV2.GL and AAV2.NN, which mediate widespread and high‐level retinal transduction after intravitreal injection in mice, dogs and non‐human primates. Importantly, both vectors efficiently transduce photoreceptors in human retinal explant cultures. As proof‐of‐concept, intravitreal Cnga3 delivery using AAV2.GL lead to cone‐specific expression of Cnga3 protein and rescued photopic cone responses in the Cnga3 −/− mouse model of achromatopsia. These novel rAAV vectors expand the clinical applicability of gene therapy for blinding human retinal dystrophies. Synopsis: Ocular gene therapy aims to improve or preserve vision in patients with inherited blinding disorders. The current technology still relies on subretinal administration of therapeutic vectors, which harbours risks of collateral damage and only treats a small portion of the affected retina. This study presents two novel engineered viral vectors capable of widespread targeting of retinal cells through a less invasive delivery route. Novel vectors AAV2.GL and AAV2.NN achieve widespread photoreceptor transduction in mouse, dog and non‐human primate after single intravitreal delivery. AAV2.GL and AAV2.NN have cone and rod photoreceptor tropism. AAV2.NN outperforms existing vectors in targeting rod photoreceptors in mice. Gene supplementation using AAV2.GL rescues cone function and CNGA3 protein expression in the Cnga3 −/− mouse model of achromatopsia. Abstract : Ocular gene therapy aims to improve or preserve vision in patients with inherited blinding disorders. The current technology still relies on subretinal administration of therapeutic vectors, which harbours risks of collateral damage and only treats a small portion of the affected retina. This study presents two novel engineered viral vectors capable of widespread targeting of retinal cells through a less invasive delivery route.